Computer Assisted Vocabulary Instruction: A Case of Applying PowerPoint Presentation into Iranian EFL Classes - Saeid Farahnia; Ali Khodi (Research in English Language Pedagogy, 2017)
Recently, with the growth of technology computer assisted language learning (CALL) has equipped teachers with new tools to transform education. In order to exploit the advantages of CALL, this study explored whether applying Power Point presentations (PPTs) brings about significant improvements in high-school learners’ English vocabulary knowledge. To this end, 120 Iranian male high-school students were divided into three experimental group and one control group. The administration of a 40- item multiple-choice vocabulary test, developed on the vocabularies to-be-instructed during the study period, demonstrated that the four groups were homogeneous in terms of their entry ability level. While all four groups received instruction in vocabulary during one and a half hour per week for six months, PPTs were employed only in the three experimental groups. Specifically, in the first group, the teacher used PPT to teach vocabulary and he exploited students’ assistance in explanation of presentation. In the second group, the students were required to prepare and present PPTs to teach vocabulary. Simultaneously, the teacher helped the students to clarify ambiguities of their presentations. The students in the third group were also demanded to have PPTs; however, the teacher did not provide them with any assistance, clarification, or explanation. Finally, the fourth group which acted as the control group was the one in which the teacher instructed vocabulary in a traditional way without the exploitation of PPT. At the end of the study, the same vocabulary test was administered as a post-test and the results of the statistical analysis indicated that the first and the fourth group significantly outperformed the other two groups.